Integrated stability control for a vehicle in the vehicle-to-grid system on low adhesion coefficient road - Wang, Yujie; Lei, Yu; Wang, Peipei (Frontiers in Energy Research, 2022)
For the vehicle-to-grid system, the dynamic performance of the vehicle in the transportation system is quite crucial. The stability of the vehicle is the basis of the whole system. Compared to the traditional vehicle, the vehicle with a torque distribution system allows the vehicle to have a better dynamic performance. The torque distribution method has attracted a lot of attention from researchers. Most of the current work focuses on the vehicle on the concrete road. To improve the vehicle lateral stability in the critical work condition, the nonlinear reference model and vehicle dynamic model with 8 degrees of freedom are established based on the vehicle dynamic theory. An integrated active front steering (AFS) and direct yaw control (DYC) controller are designed based on LQR (Linear quadratic regulator) and vehicle stability phase portrait. To evaluate the performance of the vehicle on the road with a relatively low adhesion coefficient. The double lane-change and fishhook maneuver are chosen as the work condition. The steering angle, wheel torque, vehicle routine, phase portrait track, and yaw rate are calculated and compared. The simulation result validates the effectiveness of the proposed integrated AFS and DYC control method. The stability of the vehicle on the low adhesion coefficient road can lay a good foundation of the vehicle-to-grid system.